A Model for Communication - Alli, Julie (Applied Dispute Resolution Journal, 2023)
This article describes “the Haven Communication Model,” a communication strategy that was developed by Jock McKeen and the late psychiatrist Bennet Wong in the 1970’s and 1980’s, a time that gave rise to the personal development and the self-help industry in the Western world. Much of today’s growing coaching industry owes a debt to McKeen and Wong’s path- breaking work in communication, personal develop- ment and organizational development.